ADAPTABILITY GRADATION OF DIFFERENT GENOTYPE PIGS DEPENDING ON TECHNOLOGICAL CONDITIONS - Usachova, V. Ye.; Myronenko, O. I.; Polishchuk, A. A.; Slynko, V. G.; Voloshchuk, M. V. (Scientific Progress & Innovations, 2021)
The article deals with studying the change in heat resistance of fattening pigs depending on technological conditions. The purpose and task of the conducted research were to reveal various levels of adaptability of experimental genotypes at traditional and intensive production technologies, find the impact share of genotype and environmental factors on physiological indicators of pigs. The work was conducted under traditional (before the reconstruction) and intensive (after the reconstruction) production technologies at outdoor air temperature of +23 ºС – +34 ºС on gilts aged 4-5 months. Before the reconstruction, the genotypes of Large White (LW) breed of the Ukrainian selection and Poltavska Meat (PM) breed were used; after the reconstruction, to receive fattening young pigs, the sows of Large White breed of the German selection, boars of Landrace (L) and Pietrain (P) breeds, and Cantor (C) terminal breeding boars were used. The research analysis has shown that in the pigsty, before the reconstruction, 80% of two breed crosses of LW × PM had a low adaptability; at the same time, purebred pigs of LW breed had a high (40%, adaptation index (AI) = 15.9) and average (40%, AI =9.2, Р≤0.01) adaptability. The studies have shown that after the reconstruction, the best adaptability indices were registered in pigs with (LW×L) × C genotype – 40% having high (AI=20.3) and average – 60% (AI =8.6, Р≤0.001) adaptation indices. The obtained results show that the pigs having a high adaptation level, on the average, reliably prevailed the gilts of the same age having a low adaptation level as to the body temperature indicators in the daytime by 0.32ºС (Р≤0.01), heart rate in the morning – by 65.5 beats/min (47.8%) and in the daytime – by 49.5 beats/min (14.3%, Р≤0.001), as well as adaptation index – by 15.1 units (by 4.4 times, Р≤0.001). The reliable effect has been established – 31.7–35.8 % (Р≤0.05) of the genotype on the heart rate in the groups of fattening gilts irrespective of the technological production parameters. High reliability was also registered as to the genotype influence on the heart rate in the morning and daytime before the reconstruction – 35.8, 28.0 % (Р≤0.05).